Manajemen Produksi Sayuran Organik (Kasus di Pondok Pesantren Al-Mu’minun Kelurahan Cilembang, Kecamatan Cihideung, Kota Tasikmalaya) - Imadudin, Rifki Muhamad; Firmansyah, Sani; Nuryati, Rina (Universitas Galuh, 2024)
This study aimed to determine the application of management functions in organic vegetable production at the Al-Mu'minun Islamic Boarding School, Cilembang Village, Cihideung District, Tasikmalaya City. Determining the research location was carried out purposively with the research time in September 2023 and the research method used was a case study. The analysis tool uses qualitative descriptive analysis. The variables in this research are production management which consists of planning, organizing, actuating and controlling. The results of this research show that the management function in organic vegetable production activities has been carried out at the Al-Mu'minun Islamic Boarding School. In planning, the production process has been carried out by preparing a work frame of reference (KAK) which is used as a guideline in implementing organic vegetable production, such as selecting seeds, determining planting locations and planting patterns. The organizing function in managing organic vegetable farming has also been regulated so that it can work effectively and efficiently to achieve goals. In the function of directing organic vegetable production, the foundation, including the management of the Islamic boarding school and Al-Mu'minun Vocational School, provides support by providing guidance and motivation, increasing work discipline, as well as managing harvest and marketing activities. In the production control function, observation and evaluation activities are carried out which are intended to find out data or information regarding the process of organic vegetable production activities and determine the achievement of the program objectives that have been formulated.